Comparative analysis of proprioceptive neuromuscular facilitation stretching versus foam rolling on post-exercise muscle soreness and functional recovery in university-level futsal / Muhamad Hazrul Izam Azmi ... [et al.]. - Azmi, Muhamad Hazrul Izam; Mohamed, Muhamad Noor; Azreen, Noor Azila; Safiq, Muhamad; Abu Kassim, Nurul Ain; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Muscle soreness can hinder athletic performance and recovery. This study examines the effects of Proprioceptive Neuromuscular Facilitation (PNF) stretching and foam rolling on muscle soreness among UiTM Negeri Sembilan futsal players. By identifying and comparing these methods' effectiveness, this research addresses critical gaps in understanding safe, effective recovery strategies and provides insights into optimizing post-exercise care [1]. Ten UiTM Negeri Sembilan futsal players, engaging in regular physical activity, participated in this study. Participants were instructed in proper techniques for PNF stretching and foam rolling sessions in 15 minutes targeting quadriceps, hamstrings, adductors, glutes and gastrocnemius muscles. Muscle soreness was assessed using sit-to-stand tests (pain scale), knee extensor (pain scale), and knee flexion (range of motion) across the five-time frames: pre-training, immediately post-training, 24, 48, 72 hours post-training.